'Charlotte makes me lafe [sic] sooo much': Online laughter, affect, and femininity in Geordie Shore. (1st October 2014) - Graefer, Anne
Highly successful structured reality television shows such as Geordie Shore (UK), The Only Way is Essex (UK), Made in Chelsea (UK) or Jersey Shore (US) draw audiences wide beyond their regional and national appeal, thereby exerting a considerable influence on contemporary popular culture. Lying at the intersection of documentary, soap opera and drama, reality television's specific form – its immediacy and its emotionality – invites viewers to judge and moralize the lives depicted on screen. In this article I explore the affective ways in which 'Geordie Shore' produces ideas about femininity and how comic moments in the show influence this emotive process. By analysing online comments on the show's official Facebook page I argue that the humorous quality of the text does not merely reinforce the disciplining white, middle-class gaze through which 'Geordie' femininities are produced as hypersexual(ized) ladettes worthy of social derision. Rather, the online laughter that I found in some online comments highlights that these representations are also animated through feelings of joy, affection and emotional attachment. Attending to online laughter can help us to further understand the movement between connection and disassociation through which audiences make sense of reality television.